The Analysis of Total Flavonoid Levels In Young Leaves and Old Soursop Leaves (Annona muricata L.) Using UV-Vis Sepctrofotometry Methods - Dian Anriani A. Makuasa; Purnama Ningsih (Yayasan Ahmar Cendekia Indonesia, 2020)
Soursop ( Annona muricata L.) is a type of fruit plant that contains nutrients and is a traditional medicinal ingredient that has multiple properties. This study aims to determine total flavonoid levels in young and old soursop leaf extracts using a UV-Vis spectrophotometry. Extraction of chemical content in young and soursop (Annona muricata L.) leaf extracts was carried out by maceration methos using 96% ehtanol solvent. Determination of total flavonoid levels of sample extracts was carried out through absorpation measurements at a wavelength of 432 nm. The result of the quantitative test were obtained from this study, namely total flavonoid levels in the samples of young soursop leaf extract as much as 410,833 mg/100g, whereas in large soursop leaf extract samples as many as 505,208 mg/100g.